Use of Specialized Formulas in the Enteral Nutrition of Children with Severe Neurological Diseases - O.S. Koreniuk; V.I. Ivanchenko; O.G. Alekseeva (Zaslavsky O.Yu., 2016)
The problems of nutrition of disabled children with neurological diseases - cerebral palsy and congenital anomalies of the brain were examined in the article. The features and difficulties of feeding of these patients were identified. The experience in the use of nutritive formula of full hydrolysate in the enteral feeding of the children with secondary dystrophy against the background of severe neurological pathology is presented. The efficiency of this feeding technique, a positive dynamics of nutritional status of patients were shown.